2017
DOI: 10.1016/j.tips.2017.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Targeting PAR1: Now What?

Abstract: Protease-activated receptors (PARs) are a ubiquitously expressed class of GPCRs that enable cells to respond to proteases in the extracellular environment in a nuanced and dynamic manner. PAR1 is the archetypal family member and has been the object of large-scale drug development programs since the 1990s. Vorapaxar and drotrecogin-alfa are approved PAR1-targeted therapeutics, but safety concerns have limited clinical use of vorapaxar and questions regarding the efficacy of drotrecogin-alfa led to its withdrawa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
60
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(61 citation statements)
references
References 123 publications
(130 reference statements)
1
60
0
Order By: Relevance
“…Finally, another possibility to explore is targeting the Thrombin/PAR pathway, known regulators of NOS3 in endothelial cells via phosphorylation [25], and recently identified upstream NO production also in HSCs [10]. Despite that several PAR inhibitors have been developed [26], the effect of this signaling on stem cell mobilization has only been described in the HSC compartment, thus more data are required to support its effectiveness as a niche-based therapeutic intervention.…”
Section: Editorialmentioning
confidence: 99%
“…Finally, another possibility to explore is targeting the Thrombin/PAR pathway, known regulators of NOS3 in endothelial cells via phosphorylation [25], and recently identified upstream NO production also in HSCs [10]. Despite that several PAR inhibitors have been developed [26], the effect of this signaling on stem cell mobilization has only been described in the HSC compartment, thus more data are required to support its effectiveness as a niche-based therapeutic intervention.…”
Section: Editorialmentioning
confidence: 99%
“…Cleavage of endothelial PAR1 by thrombin results in apoptosis, release of granules, surface expression of inflammatory markers, and loss of barrier function. 2 In contrast, cleavage of PAR1 by activated protein C (APC) can result in protection from apoptotic stimuli, suppression of inflammatory markers, and fortification of barrier function. 2 These observations raise the complex question of how endothelial cells integrate PAR1 stimulation to mediate such varied responses.…”
mentioning
confidence: 99%
“…3,11 APC, matrix metalloproteinase 1, proteinase 3, and neutrophil elastase all cleave PAR1 at distinct sites. 2 Peptides based on these non-canonical tethered ligands stimulate PAR1. When the authors compared the different PAR1-stimulating peptides to SFLLRN, they found that changes in the phosphoproteome induced by exposure to non-canonical peptides were minor compared with the robust changes induced by SFLLRN and changes were generally in the same direction for both SFLLRN and non-canonical ligands.…”
mentioning
confidence: 99%
“…We know now that PARs can be activated or inactivated by a myriad of different serine proteases and matrix metalloproteinases, and that PARs can orchestrate differential "biased" cellular signaling responses to different proteases. 3 For example, thrombin cleaves PAR-1 at arginine 41 and stimulates proinflammatory signaling pathways, whereas aPC cleaves at arginine 46 and directs anti-inflammatory responses 4 (see figure).…”
mentioning
confidence: 99%
“…n Complement and coagulation: so close, yet so far T heir observation appears in sharp contrast with earlier studies that did identify a potential for thrombin and plasmin to activate the complement system. 2,3 The apparent contradiction thus raises a fundamental question: Is this a case of "in vivo veritas," or are there experimental or physiological grounds that may explain the differences? One infamous setting where activation of complement, coagulation, and fibrinolysis coincide is sepsis.…”
mentioning
confidence: 99%